EKOWISATA DAN DAYA DUKUNG CAGAR ALAM MUTIS DI KABUPATEN TIMOR TENGAH SELATAN, PROPINSI NTT - Seo, Noni Andriane (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2023)
Mutis Nature Reserve in the Middle South of Timor Regency is one of the prospective areas that can be explored for ecotourism. Ecotourism means that the visitors can enjoy the tourist attractions in a tourist destination while making positive contributions to the local people, economically, without ruining the resources or at least being able to minimize the negative impact on the environment of the tourist destination area. Generally, the aim of this research was to discover the potential resources of Mutis Nature Reserve that could be explored for ecotourism. The method that’s been used for this research was by using the qualitative method to discover the potential ecotourism in Fatumnasi and also by using Carrying Capacity Calculation to measure the Carrying Capacity of Mutis Nature Reserve. Data were collected by observation method and using in-depth interviews with the key informant. Some of the research results indicated that the resources of Mutis Nature Reserve can be explored for ecotourism. It also indicated that the exploration and development must be based on effective carrying capacity to maintain the resources of the tourist attractions on a certain level of management. The Carrying Capacity that’s been measured in this research is 1). Physical Carrying Capacity, 2). Real Carrying Capacity,3). Effective Carrying Capacity Suggestions were given for the improvement of the public infrastructures, tour packages should be available and so are the trained local guides, the planning and development of the ecotourism should involve the local community.